2019
DOI: 10.1186/s12871-019-0903-7
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesiology and cognitive impairment: a narrative review of current clinical literature

Abstract: Background: The impact of general anesthesia on cognitive impairment is controversial and complex. A large body of evidence supports the association between exposure to surgery under general anesthesia and development of delayed neurocognitive recovery in a subset of patients. Existing literature continues to debate whether these short-term effects on cognition can be attributed to anesthetic agents themselves, or whether other variables are causative of the observed changes in cognition. Furthermore, there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 117 publications
2
119
1
3
Order By: Relevance
“…Cognitive changes after anesthesia also include postoperative neurocognitive disorders. Specific risk factors for such disorders should be evaluated in susceptible patients [148,149].…”
Section: Strength Of Recommendationmentioning
confidence: 99%
“…Cognitive changes after anesthesia also include postoperative neurocognitive disorders. Specific risk factors for such disorders should be evaluated in susceptible patients [148,149].…”
Section: Strength Of Recommendationmentioning
confidence: 99%
“…[ 26 ] Especially in elderly patients, the functions of tissues and organs of elderly patients gradually decline, their tolerance to surgery and anesthesia decreases accordingly. [ 27 ] Previous study [ 28 ] has reported that the incidence of POCD in elderly patients after receiving general anesthesia can be as high as 20%. With the improvement of peoples living standards and the advancement of endoscopy technology, the attention to the physical and mental recovery of patients after surgery has gradually increased among the health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…However, propofol is structurally unrelated to other hypnotic compounds. It induces hypnosis rapidly and reliably, and has additive or synergistic hypnotic effects with many other agents (like barbiturates, benzodiazepines, opioids and ketamine) commonly used in anesthesia [88].…”
Section: Propofolmentioning
confidence: 99%